More than credit: Exploring associations between microcredit programs and maternal and reproductive health service utilization in India - Nabamallika Dehingia; Abhishek Singh; Anita Raj; Lotus McDougal (Elsevier, 2019)
Microcredit programs are increasingly popular interventions aimed at enabling women's economic empowerment in low- and middle-income countries. Resultant improved income, and social support from co-members of microcredit programs, may lead to increased utilization of health services. But existing research is inconclusive. This study investigates the association of microcredit program awareness and participation, with maternal and postpartum reproductive health service utilization in India. We use data from a nationally representative survey, the National Family Health Survey (2015-16), and assess three indicators of maternal health service utilization: receipt of four or more antenatal check-ups, institutional delivery, and postnatal check-up among women who had a child less than 5 years of age (N = 32,880). Reproductive health service utilization is assessed via postpartum contraceptive use within 12 months of childbirth, among women who had a live birth in the 12-59 months preceding the survey (N = 24,258). We use binomial and multinomial logistic regression models to examine associations. Additionally, we use propensity score matching to account for self-selection bias. One-third of women are aware of microcredit programs in their community/village, but only 6% have ever taken a loan from these programs. Both microcredit program awareness and participation are associated with higher odds of antenatal care, postnatal check-ups, as well as use of a modern method of contraceptive within 12 months of childbirth, even after accounting for self-selection bias. Stratified analysis by household wealth show that significant associations seen in our primary analyses are significant only for the poorest women. Findings highlight the potential value of microcredit programs in improving health service utilization during and after pregnancy, particularly among poor women. Microcredit program benefits extend beyond their participants. Non-participants living close to the programs also have greater odds of maternal and reproductive health service utilization, suggesting a spillover effect of these programs at the community level. Keywords: Microcredit program, Financial inclusion, India, Maternal health, Postpartum contraceptive